Implementasi Model Pembelajaran Berbasis Proyek untuk Meningkatkan Kompetensi Siswa di Sekolah Kejuruan Negeri 1 Pariaman - Sabrianto, Jerry; Primawati, Primawati; Wulansari, Rizky Ema; Yuvenda, Dori (Lembaga Yasin AlSys, 2026)
Although the Project Based Learning (PjBL) model has been widely introduced in vocational education, studies that specifically analyze its effectiveness in improving student competence in the Basic Mechanical Engineering Design (PDTM) subject at vocational high schools remain limited. This study aimed to analyze the effectiveness of the Project Based Learning model in improving the competence of Grade X students in the Mechanical Engineering expertise program at SMK Negeri 1 Pariaman in the PDTM subject. The research employed a Classroom Action Research design implemented in two cycles, each consisting of planning, implementation, observation, and reflection stages. Through this approach, students were actively engaged in project-based tasks that enabled them to apply theoretical knowledge in practice. The findings showed a significant increase in students’ affective participation, psychomotor skills, and academic achievement. Quantitatively, the proportion of students achieving mastery increased from 40% in the first activity to 88.57% in the subsequent activity, while the average student score rose from 67.48 to 83.6. These results indicate that Project Based Learning is an effective instructional approach for developing students’ critical thinking, innovation, teamwork, and practical competence, thereby better preparing them to meet the demands of the modern industrial sector.